Use of GIS for the development of digital structural integrity maps of high risk areas in Cyprus due to corrosion of steel reinforcement - Christofe, Andreas; Neocleous, Kyriacos; Themistocleous, Kyriacos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2013)
Concrete reinforced with steel rebars remains one of the most widely used construction materials. Despite its good mechanical performance and expected service life of at least 50 years, reinforced concrete is subjected to corrosion of the steel rebars which normally leads to concrete spalling, deterioration of the reinforced concrete’s (RC) mechanical properties and eventual reduction of the structural load capacity. In Cyprus, especially in coastal regions where almost 60% of the population resides, many structural problems have been identified in RC structures, which are caused by the severe corrosion of steel rebars. Most RC, located in coastal areas, show signs of corrosion within the first 15-20 years of their service life and this affects their structural integrity and reliability, especially against seismic loading. This paper presents the research undertaken as part of the ‘STEELCOR’ project which aims to extensively evaluate the steel corrosion of RC buildings in coastal areas of Cyprus and conduct a risk assessment relating to steel corrosion. GIS are utilized in conjunction with non-destructive testing of corroded RC structures to develop a digital structural integrity map of Cyprus which shows the areas with high risk of steel corrosion of RC buildings. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: Corrosion; Geographic information systems; Buildings; Nondestructive evaluation; Reliability